Integrative omic systems: a holistic, innovative and sustainable vision for feeding the world in 2050? (Orinoquia, 2021)
The relationships that human beings have built with microorganisms, plants and animals have enabled our modernsociety to develop technologically. Human populations in ancient times fed themselves by hunting, fishing, gatheringplants and/or their products. Subsequently, organisms began to be domesticated for food crops in the earlyHolocene period (~11,700 years ago); however, it was not until the beginning of the Neolithic era (~10-11 thousandyears ago) that rudimentary technology was developed for such purpose. These conditions enabled the emergenceof agriculture-based societies in Eurasia, North Africa and Central and South America. The beginnings of aquaculturedate back around 4,000 years ago in China. Since their origins, such ancient activities have motivated humanbeings to create technological systems for improving crop production rates and meeting food demand. It is thus nocoincidence that many modern technological and scientific advances are linked to applications for agricultural andaquaculture production.A considerable increase in the human population (9.9 billion people) is expected by 2050 according to various internationalorganisations; this will be accompanied by the consequent increased demand for food and environmentalresources. Some strategies have even begun to be developed to avoid food shortages during the next three decades;increasing crop yields and improving global food production systems are priorities imposed by such scenario. Betterunderstanding of genes and genomes’ functional structure, along with organisms’ physiological responses to dietaryand/or environmental changes is required for achieving such goals.Humanity’s access to a large amount of information has increased substantially during recent decades; biologicalsciences have not been the exception. A holistic approach called Systems Biology currently uses mathematical modelsto represent the interactions of elements influencing biological processes. Emerging omic technologies/sciencesand data analysis techniques can be used to understand molecular phenomena; omics-based analysis enables quantifyingand characterising the groups of molecules involved in the structure or biological function of a cell, tissue ororganism regarding a particular time and set conditions.Genomics, proteomics and metabolomics are omic sciences that study genes, proteins and metabolites’ molecularrelationships with a determined final phenotype. The three main omic sciences have engendered many offshoots;some of the most commonly used ones are transcriptomics which studies which genes are active or expressedand epigenomics which studies how DNA-related gene activity or expression is controlled. Both disciplines helpto describe how the environment (medicines, diet, behaviour, interactions, radiation, climate, pollution) modulatesthe expression of certain genes. Microbiomics studies microorganism population changes in various environments(soil, water, air, food, animal bodies) when an external factor changes their quality or quantity (feeding, temperature,photoperiod, social interaction).The genomic sequences for some organisms and microorganisms cultivated around the world have been obtained inrecent years; this information has been used to assess their molecular architecture, structure and complexity, as wellas for describing certain of their unique genomic features. Molecular markers have been identified in some terrestrialand aquaculture organisms’ genetic lines, enabling specific genes to be connected with phenotypical characteristicsregarding production performance and significant economic traits (better feed conversion rates, accelerated growth,reproductive efficiency, product quality, susceptibility to diseases).